Introduction: New Geographies of Scandinavian Studies. Moving maps, reciprocal images, emerging communities - Jelsbak, Torben; Körber, Lill-Ann (Folia Scandinavica Posnaniensia, 2023)
This article provides an introduction to the Research Network “New Geographies of Scandinavian Studies” while at the same time discussing some of its main concerns and questions: the position of the Nordic countries and the role of Scandinavian Studies in the changing geopolitical landscape of post-Cold War Europe. The collapse of the Eastern bloc in 1989–1991 led to a reconfiguration of the European political map. This situation also entailed new possibilities for international and cross-disciplinary research: A new understanding of Nordic and Baltic studies was institutionalized and new regional concepts were developed as alternatives to Cold War geopolitics. The network “New Geographies of Scandinavian Studies” is rooted in this ongoing reorientation of the field. The article discusses some of the potentials and challenges of this new agenda of Scandinavian Studies in the context of the new geopolitical confrontation between Russia and the West after Russia’s military attack on Ukraine in February 2022.